On determining soot maturity: A review of the role of microscopy- and spectroscopy-based techniques. (August 2020) - Baldelli, Alberto; Trivanovic, Una; Sipkens, Timothy A.; Rogak, Steven N.
Abstract: Incomplete combustion is the main source of airborne soot, which has negative impacts on public health and the environment. Understanding the morphological and chemical evolution of soot is important for assessing and mitigating the impact of soot emissions. Morphological and chemical structures of soot are commonly studied using microscopy or spectroscopy, and the best technique depends on the parameter of interest and the stage of soot formation considered (i.e., maturity). For the earliest stages of soot formation, particles exhibit simple morphology yet complex and reactive chemical composition, which is best studied by spectroscopic techniques sensitive to the large number of soot precursor species. The only microscope that can offer some morphological information at this stage is the scanning probe microscopy, which can image single polycyclic aromatic hydrocarbons, the precursors of soot. A broader range of types of spectrometers and microscopes can be used by increasing the soot maturity. Mature soot is primarily carbon, and exhibits complex fractal-like morphology best studied with electron microscopy and techniques sensitive to thin oxide or organic coatings. Each characterization technique can target different morphological and chemical properties of soot, from the early to the late stage of its formation. Thus, a guideline for the selection of the appropriate technique can facilitates studies on environmental samples involving the presence of soot. Highlights: Microscopes and spectrometers to evaluate soot maturity. STM and FTIR are, respectively, to use for image and determine PAH in incipient soot. HIM measures morphological parameters in young soot minimizing sample damage. Raman spectrometer analyzes changes in the chemistry of soot through its formation.